Research on Herbal Therapies for Osteoarthritis in 2004–2022: A Web of Science-Based Cross-Sectional Bibliometric Analysis. (30th July 2022) - Song, Weijiang; Chen, Jiaqi; Yang, Guoyan; Liao, Jiahe; Shen, Hongbo; Li, Sai; Ding, Ning; Li, Dong
Abstract : Objective . The extent, range, and nature of available research in the field of herbal therapies for osteoarthritis (OA) have not been systematically analyzed. This study aimed to map the literature available on herbal therapies for OA and identify global hotspots and trends in this field. Methods . Studies on herbal therapies for OA published between 2004 and 2022 were searched from the Web of Science Core Collection. Microsoft Excel, SPSS Statistics, and CiteSpace software were used to analyze and visualize the quantity and citations of publications, and the research hotspots and trends in research on herbal therapies for OA. Results . A total of 1649 publications mainly from 76 countries/regions and 270 institutions were included in this study. From 2004 to 2022, there is an upward trend in the publications of herbal therapies for OA. China ranked first in the number of publications ( n  = 568, 34.45%), followed by the USA ( n  = 353, 21.41%), South Korea ( n  = 187, 11.34%), Germany ( n  = 85, 5.15%), and England ( n  = 79, 4.79%). Kyung Hee University ( n  = 46), Xianxiang Liu ( n  = 25), and Evidence-Based Complementary and Alternative Medicine ( n  = 74) were the most prolific affiliation, author, and journal, respectively. Felson DT ( n  = 185) and Arthritis and Rheumatism ( n  = 1173) held the record for the most cited papers by an author and journal, respectively. Currently, the hot keywords in the field of herbal therapies for OA include knee OA, traditional Chinese medicine (TCM), differentiation, rosa canina, inflammation, oxidative stress, stem cell, and regenerative medicine. The emerging research trends in herbal therapies for OA are herbal medicinal product, chronic knee pain, mesenchymal stem cell, and clinical pharmacology. Conclusions . Research on herbal therapies for OA is flourishing, but communication among countries/regions should be strengthened. Current research on herbal therapies for OA mainly focuses on knee OA, TCM, differentiation, rosa canina, inflammation, oxidative stress, stem cell, and regenerative medicine. The research frontiers are herbal medicinal product, chronic knee pain, mesenchymal stem cell, and clinical pharmacology.